Physical-virtual window: a social interaction resource for use in XR environments - Soares, Marcos Felipe; Toledo, Ana Júlia; Padilha, Rafael; Franco, Guilherme C.; Nascimento, Hugo; Salles, Laurita R.; Berretta, Luciana O.; Souza, Alércio R. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15788, 2025)
In immersive environments such as the metaverse, user interaction with the virtual space has been shown to increase engagement and a sense of belonging to the experience. By integrating a window from the physical world into the digital environment, not only are the means of interaction amplified, but a dynamic connection between multiple realities is also created, allowing them to intersect through this resource. In this paper, we propose the creation of a window that transmits spatial audio and video from the physical environment to a space in the metaverse and vice-versa. We also analyze the initial user perception and the limitations imposed by current technology.